A new way to regulate inflammation: selective autophagic degradation of IKKγ mediated by ANGPTL8 - Zhang, Yu (Cell Stress, 2018)
Transcription factor nuclear factor-κB (NF-κB) plays pivotal roles in the regulation of inflammation and immunity. However, the precise mechanism of NF-κB activation is not fully elucidated. We recently found that Angiopoietin like protein 8 (ANGPTL8, also known as Lipasin, RIFL, TD26 or C19orf80), which is a previously identified secreted metabolic regulator, also can work intracellularly as a negative feedback inhibitor of NF-κB activation. Mechanistically, ANGPTL8 is induced by TNFα stimulation, a classic inducer for NF-κB activation; then, the intracellular ANGPTL8 self-associates via its N-terminal region and interacts with Sequestosome-1 (p62/SQSTM1). The resulting ANGPTL8-p62 aggregates work as a platform in the recruitment and autophagic degradation of IκB kinase gamma (IKKγ/NEMO). Consistently, in patients diagnosed with infectious diseases, enhanced circulating ANGPTL8 levels were detected. These findings suggest a new role for selective autophagy in the regulation of signal transduction and inflammation.